Linking Oxidative Stress and DNA Damage to Changes in the Expression of Extracellular Matrix Components - Martins, Susana G.; Zilhão, Rita; Thorsteinsdóttir, Sólveig; Carlos, Ana Rita (Frontiers in Genetics, 2021)
Cells are subjected to endogenous [e.g., reactive oxygen species (ROS), replication stress] and exogenous insults (e.g. ultra-violet light, ionizing radiation, certain chemicals), which can affect the synthesis and/or stability of different macromolecules required for cell and tissue function. Oxidative stress, caused by excess ROS, and DNA damage, triggered in response to different sources, are countered and resolved by specific mechanisms, allowing the normal physiological equilibrium of cells and tissues to be restored. One process that is affected by oxidative stress and DNA damage is extracellular matrix (ECM) remodeling, which is a continuous and highly controlled mechanism that allows tissues to readjust in reaction to different challenges. The crosstalk between oxidative stress/DNA damage and ECM remodeling is not unidirectional. Quite on the contrary, mutations in ECM genes have a strong impact on tissue homeostasis and are characterized by increased oxidative stress and potentially also accumulation of DNA damage. In this review we will discuss how oxidative stress and DNA damage affect the expression and deposition of ECM molecules and conversely how mutations in genes encoding ECM components trigger accumulation of oxidative stress and DNA damage. Both situations hamper the reconstitution of cell and tissue homeostasis, with negative impacts on tissue and organ function, which can be a driver for severe pathological conditions.